Exploring Factors Influencing Medication Compliance in Saudi Rheumatoid Arthritis Patients: A Nationwide Cross-Sectional Survey – Results from the COPARA Study - Omair,Mohammed A; Alshehri,Maha M.; Altokhais,Nouf; Aljanobi,Ghada A; El Dessougi,Maha I; AlHarthi,Amal; Omair,Maha A; Attar,Suzan M; Bahlas,Sami M; Alfurayj,Abdullah S; Alazmi,Mansour; Asiri,Alhussain M; et al. (Patient Preference and Adherence, 2022)
Mohammed A Omair,1 Maha M Alshehri,2 Nouf A Altokhais,2 Ghada A Aljanobi,3 Maha I El Dessougi,4 Amal AlHarthi,4 Maha A Omair,5 Suzan M Attar,6 Sami M Bahlas,6 Abdullah S Alfurayj,7 Mansour S Alazmi,8 Alhussain M Asiri,9 Mohammed M AlOmair,9 Lobna Al Juffali,10 Haya M Almalag10 1Rheumatology Unit, Department of Medicine, King Saud University, Riyadh, Saudi Arabia; 2College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 3Rheumatology Unit, Department of Medicine, Qatif Central Hospital, Qatif, Saudi Arabia; 4Rheumatology Unit, Department of Medicine, Security Forces Hospital, Riyadh, Saudi Arabia; 5Department of Statistics and Operations Research, College of Science, King Saud University, Riyadh, Saudi Arabia; 6Rheumatology Unit, Department of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 7Rheumatology Unit, Department of Medicine, Buraidah Central Hospital, Buraidah, Saudi Arabia; 8Rheumatology Unit, Department of Medicine, Prince Mohammed Medical City, Sakaka-Aljouf, Saudi Arabia; 9Rheumatology Unit, Department of Medicine, Aseer Central Hospital, Abha, Saudi Arabia; 10Department of Clinical Pharmacy, College of Pharmacy, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Mohammed A Omair, Rheumatology Unit, Department of Medicine, King Saud University, Riyadh, Saudi Arabia, Tel +966505270513, Email momair@ksu.edu.saPurpose: Compliance is essential to achieve treatment goals in rheumatoid arthritis (RA) patients. The current study evaluated compliance and related factors in a large and diverse population.Patients and Methods: Patients with RA who received active treatment were invited to participate in an online survey. The Arabic versions of the 5-Item Compliance Questionnaire for Rheumatology (ACQR-5) and the RA Impact of Disease (RAID) were used to measure compliance and disability, respectively. The patients were sub-grouped based on background disease-modifying anti-rheumatic drugs (DMARDs). Variables associated with high compliance were selected for the logistic regression ...